(untitled) (Global Journal of Human-Social Science, 2026)
This article presents a comparative analysis between Brazilian Sign Language (Libras) and Quebec Sign Language (LSQ), highlighting their historical, sociocultural, and political contexts. The study is grounded in a mixed approach that combines bibliographic research with field experience developed through an academic partnership between the Federal Institute of Paraná (IFPR), Curitiba campus, and the Université de Montréal (UdeM). As part of this experience, the research included a technical visit to the university, as well as direct contact with Deaf individuals and sign language interpreters who use LSQ in educational and social contexts. From this perspective, the article examines structural similarities and articulatory differences between Libras and LSQ, while also addressing their respective trajectories of recognition and affirmation. Beyond linguistic aspects, the study emphasizes the central role of these languages in the construction of Deaf identity and in the promotion of social inclusion. The discussion reinforces the idea that, despite their regional and cultural specificities, both languages share a common purpose: to ensure accessibility, visibility, and dignity for the Deaf communities they represent.